Tourism Carrying Capacity to Support Beach Management at Tanjung Bira, Indonesia - Maryono Maryono; Hefni Effendi; Majariana Krisanti (Jurnal Segara, 2019)
Tourism carrying capacity assessment for the protection of coastal area was applied to Tanjung Bira beach as an attempt to assess the optimum allowable number of visitors in accordance to the PAOT (people at one time approach) without damaging the surrounding ecological, social and cultural environments. The study shows that the Real Carrying Capacity (RCC) was 202 beach user/day and the Effective Carrying Capacity (ECC) was 117 beach user/day. Although there was a significant difference between Physical-Ecological and Social-Cultural Carrying Capacity, this study suggests that the Physical-Ecological Carrying Capacity or Real Carrying Capacity may be applied for ecosystem management, whilst the Social-Cultural Carrying Capacity or Effective Carrying Capacity (ECC) may be addressed when management objectives are tourists and beach user.